DIRECTIVE SPEECH ACTS IN LECTURES OF INDONESIAN LANGUAGE LEARNING MODELS ON CLASS P2TK - Nurul Haeniah; Agus Nasir; Andi Saadilah (Sean Institute, 2022)
Communication events that occur during the learning process are characterized by speech acts that are established between the teacher and students. One form of speech acts is directive speech acts, these speech acts are used by teachers whose function is to get students to do something. The problem examined in this study is the form and function of the teacher directive speech acts in the lecture discourse of the learning model in the P2TK class. This study uses a descriptive qualitative research approach to the type of microetnographic research. Existing data in the form of verbal speech containing directive speech acts. Sources of research data obtained from teacher speech in the classroom. Data collection techniques in this study use the method of listening with the ability to engage in engaging, and to analyze the data, theoretically this study uses an interactive model, which is in accordance with the social context in classroom interactions (Milles and Huberman, 1992: 20), the results This research is in the form of (1) directive speech acts in the form of requests (2) directive speech acts in the form of invitations / invitations, (3) directive speech acts in the form of urges / encouragement, (4) directive speech acts in the form of questions, (5) directive speech acts in the form of orders , (6) directive speech acts in the form of prohibitions, (7) and directive speech acts in the form of allow.